2016
DOI: 10.14393/bj-v32n2a2016-29572
|View full text |Cite
|
Sign up to set email alerts
|

Pattern analysis of multi-environment trials in common bean genotypes

Abstract: ABSTRACT:The aim of this study was to use the patterns analysis technique to investigate the grain yield of 13 common bean genotypes evaluated in 12 environments in the State of Mato Grosso do Sul, under presence of genotype x environment interaction (G x E). The trials were conducted between the years 2000-2006 at Universidade Estadual de Mato Grosso do Sul, Unit of Aquidauana, and at Faculdade de Ciências Agrárias da Universidade Federal da Grande Dourados. Have been identified nine groups of genotypes and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Because environmental conditions for testing are distinct, the genotype by environment interaction (G x E) affects the agronomic performance, and thus, it is necessary to analyze the stability of genotypes across environments [16,17]. This allows the assessment of the real impact of selection and ensures high reliability in the genotype recommendation for a specific place or environment groups [18,19]. Another key reason for the G x E analyses in bean breeding in Africa is that lines adapted to an African bean environment (AFBE) can be grown in similar areas in other parts of Africa [20].…”
Section: Introductionmentioning
confidence: 99%
“…Because environmental conditions for testing are distinct, the genotype by environment interaction (G x E) affects the agronomic performance, and thus, it is necessary to analyze the stability of genotypes across environments [16,17]. This allows the assessment of the real impact of selection and ensures high reliability in the genotype recommendation for a specific place or environment groups [18,19]. Another key reason for the G x E analyses in bean breeding in Africa is that lines adapted to an African bean environment (AFBE) can be grown in similar areas in other parts of Africa [20].…”
Section: Introductionmentioning
confidence: 99%
“…This variation indicated that there was contrast among environments and the occurrence of differential response of the genotypes to environmental effects. The environment was the source of variation most contributed to the performance of genotypes, indicating that the edaphic and agro climatic features of each environment significantly interfered in the trait measured [17]. The interaction between genotype x environment factors indicated that the effects of all variations were not explained individually for characters under study, and the effect provided by the environment condition promoted differences in expression of these traits [18].…”
Section: Location 3: High Altitudementioning
confidence: 99%
“…These results could be caused by edaphoclimatic variations, as well as variations in the incidence of pests and diseases in the environments in which the cultivars were evaluated, resulting in GEI. Several authors have also previously [52][53][54][55] reported the influence of these factors on the environmental classification, resulting in significant GEI. For Ramalho et al [56], the most significant contributions to the GEI in the common bean culture were due to the combinations of cultivar × season and cultivar × years.…”
Section: Plos Onementioning
confidence: 99%